"Going global" and FDI inflows in China: "One Belt & One Road" initiative as a quasi‐natural experiment. (25th April 2019) - Luo, Changyuan; Chai, Qingyuan; Chen, Huiyao
Abstract: This paper investigates the impact of "One Belt & One Road" as an exogenous policy shock on the utilisation of foreign capital in China in the short term. Based on provincial panel data for the years 2003–15, the empirical study is conducted with difference‐in‐differences design. The first difference is whether a province is an OBOR province, and the second is whether "One Belt & One Road" initiative has been proposed. The empirical results suggest the utilisation of foreign capital in OBOR provinces has decreased significantly compared to non‐OBOR provinces after the initiative has been proposed. The study has further shown that the OBOR construction not only means factor movements and projects but also stands for policy shock. Its impact on utilisation of foreign capital cannot be simply captured by the commonly quantifiable "going global" indicators, namely outward direct investment, overseas contracted projects or overseas labour services. The negative impact of the initiative on foreign capital utilisation is strongly reflected in the OBOR provinces with low levels of economic development, heavy fiscal burdens and high proportions of state‐owned economy. In the short term, the negative impact of the initiative on foreign capital utilisation may be due to its role in resource competition and signal delivering. The former means that the OBOR initiative may induce resource competition between "going global" and "bringing in, " and the latter suggests that this initiative is likely to be regarded as a "signal" by foreign investors that "going global, " not "bringing in, " has become the priority of the government.